HistÓrias e identidade de professores bacharÉis que atuam em cursos de formaÇÃo de professores: As relações curriculares entre a “Licenciatura” e o “Bacharelado” nas trajetórias formativas - Pereira, Diego Carlos [UNESP]; Da Costa, Váldina Gonçalves (My University, 2019)
The article discusses the training of bachelor's teachers who work in teacher's training undergraduate courses of a public institution. The purpose of the text is to ponder and list the characteristics that contextualize the relationship of trainer professors and their bachelor's formation with the professional teaching performance in teacher training courses, considering their formative trajectories and professional experiences as social and biographical elements which constitute the identity of these persons. Through Oral History, five training teachers were interviewed and the results show that the formative experiences, whether at the bachelor's degree or in the postgraduate level, are biographically articulated to the successive processes of personal and institutional socialization of the professors. Both bachelor's degree and postgraduate courses are not isolated processes and construct dynamic professional acts of belonging and are situated in the context of institutions and the lives of employees. They are experiences filled with emotions, traumas, decisions, uncertainties, overcomes and achievements that are inherent to the constitution of the identity of these teachers and permeate the conflicting relationship between the curricular relationship of “Teacher's training degree” and “Bachelor's degree”.
Keywords: Bachelor's degree; Professor's trainer; Teacher's training degree